SEJARAH DAN DINAMIKA PIMPINAN CABANG MUHAMMADIYAH KEBAYORAN BARU - Mukhlish Muhammad Maududi; Mohammad Supendi (Universitas Muhammadiyah Prof Dr Hamka, 2020)
Muhammadiyah Kebayoran Baru Branch is one of the oldest branches in Jakarta, with a well-developed Charity Business, such as Leading Schools and Hospitals and the success of organizing da'wah, is also the place for the establishment of the Muhammdiyah Vigilance and Preparedness Command